Luminescent tungsten() complexes as photocatalysts for light-driven C-C and C-B bond formation reactions - Yu, Daohong; To, Wai-Pong; Tong, Glenna So Ming; Wu, Liang-Liang; Chan, Kaai-Tung; Du, Lili; Phillips, David Lee; Liu, Yungen; Che, Chi-Ming (Chemical science (Cambridge), 2020)
The realization of photocatalysis for practical synthetic application hinges on the development of inexpensive photocatalysts which can be prepared on a large scale. Herein an air-stable, visible-light-absorbing photoluminescent tungsten( vi ) complex which can be conveniently prepared at the gram-scale is described. This complex could catalyse photochemical organic transformation reactions including borylation of aryl halides, such as aryl chloride, reductive coupling of benzyl bromides for C-C bond formation, reductive coupling of phenacyl bromides, and decarboxylative coupling of redox-active esters of alkyl carboxylic acid with high product yields and broad functional group tolerance. A luminescent tungsten( vi ) complex catalyses a broad spectrum of light-driven organic transformation reactions with high product yields and good functional group tolerance.